PENDIDIKAN KESEHATAN DAN DEMONTRASI INTERVENSI PEMBERIAN MEDISCO PADA BALITA BERAT BADAN KURANG USIA 12-59 BULAN - Sutiyono; Riska Indrayati; Rizki Sahara; Dhiyan Nany Wigati; Nurul kodiyah; Sri Untari; Sri Temu; Muhammad Makmun; Rahmawati; Nurya Kumalasari; Suryani; Wahyu Riniasih; Febriana Tri Kusumawati (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: Malnutrition is a condition of a person whose nutritional deficiency is below average. In Indonesia, the prevalence of toddlers experiencing nutritional problems is 17.7%. The prevalence of nutritional problems consists of malnutrition of 3.9% and malnutrition of 13.8%. Toddlers aged 12-59 months are an age group that is vulnerable to health and nutritional disorders.   Objective: The objective of this service is to increase mothers' knowledge of the Medisco concept and the practice of making Medisco.   Results: The implementation of health education was achieved 100% with the community understanding the use of the medisco concept and the medisco manufacturing method. After the demonstration of making Medisco was carried out, mothers were willing to implement the utilization of the achievements of the medisco concept process and the medisco manufacturing method.